FASHION DESIGN CREATIVITY IN THE DIGITAL ERA: THE INFLUENCE OF AI ON PINTEREST, DESIGN APPS, AND K-POP TRENDS - Sriwahyuningsi Hamar; Nurul Hidayati; Muhammad Aris Ichwanto; Marsono; Inas Amatullah (SOSIOEDUKASI, 2026)
Study This aim For analyze influence Pinterest AI usage , app digital design , and K-pop trends towards creativity design fashion Vocational high school students majoring in Fashion Design. Research use approach quantitative with method survey correlational , involving 232 students from three different vocational schools . Data analyzed use Structural Equation Modeling (SEM) via device AMOS software . Research results show that Pinterest's use of AI has influence significant to use application digital design and in direct increase creativity design fashion students . Application digital design is also proven give contribution positive to creativity student in designing fashion . Although K-pop trend is not show influence significant direct​ to creativity , but own potential influence No direct through improvement Pinterest AI usage and apps design . findings This indicates that integration digital technology and culture popular can be an effective strategy in increase competence creative students in the field design fashion . Research This give implications important for development curriculum and learning strategies that are oriented towards needs digital fashion industry .